Influence of Land Management Systems in Utilization of Residual and Soil Moisture of Harvested Paddy Field - Chakraborty, P.B.; Maiti, D. (Journal of Soil and Water Conservation, 2022)
Field experiments were conducted during winter seasons of 1994-95 and 1995-96 with the aim to study the influence of tillage along with mulch on utilization of residual soil moisture of harvested wet-season paddy field. Lentil and Mustard were grown as test crops. Result shows that minimum tillage along with mulch proved better over other land management system as regard conservation of residual soil moisture for a longer period. However, combination of strip-tillage and paddy straw mulch had highest (81%) moisture conservation efficiency. • Mulch in addition to minimum tillage found beneficial in maintaining soil salinity below 2.0dStrid . The high moisture conservation as well as low salinity under the same management system improved grain yield of the crops. The yield increments over conventional tillage Were 60.0 and 54.8 per cent for lentil and mustard respectively. Similar trend was observed in moisture-use-efficiency.